Monolayer AgBiP2Se6: an atomically thin ferroelectric semiconductor with out-plane polarization. Issue 24 (12th June 2017) - Xu, Bo; Xiang, Hui; Xia, Yidong; Jiang, Kun; Wan, Xiangang; He, Jun; Yin, Jiang; Liu, Zhiguo
Abstract : Using first-principles calculations, we designed a two-dimensional material, monolayer AgBiP2 Se6, with the thickness of only 6 Å, which exhibited out-plane ferroelectricity. Abstract : Using first-principles calculations, we designed a two-dimensional material, monolayer AgBiP2 Se6, with the thickness of only 6 Å, which exhibited out-plane ferroelectricity. The ground state of the monolayer AgBiP2 Se6 was not purely ferroelectric since the out-plane ferroelectricity originated from the compensated ferrielectric state: the off-centering antiparallel displacements of Ag + and Bi 3+ ions. The compensated ferrielectric ordering has superiority on reducing the depolarization field to stabilize the ferroelectricity. Furthermore, together with strong visible-light adsorption and suitable band edge alignments, we proposed the monolayer AgBiP2 Se6 as a visible-light photocatalyst for water-splitting as the out-plane polarization could enhance the electron–hole separation. Our results offer a new way to overcome the critical thickness limitation of nanoscale ferroelectrics. The out-plane ferroelectricity in monolayer AgBiP2 Se6 has great potential for developing various devices with desirable applications.